The Application of the Concept of Asymmetric Decentralization in Local Government Governance - Isra Muksin; Masyur Djamal (Pt. Anagata Sembagi Education, 2026)
Asymmetric decentralization has emerged as an increasingly important framework for accommodating the political, fiscal, cultural, and historical diversity of subnational regions within unitary states. Unlike symmetric decentralization, which grants uniform authority to every local government, asymmetric decentralization allows a differentiated distribution of governmental authority based on the specific needs, historical claims, and administrative capacities of particular regions. This study examines the application of the concept of asymmetric decentralization in local government governance through a qualitative, normative-juridical, and comparative case study approach, drawing on twenty-five peer-reviewed academic sources published between 2021 and 2026. The analysis centers on special autonomy arrangements in Papua, Aceh, and Yogyakarta, Indonesia, and is triangulated against comparative international cases, including Pattani in Thailand, the Anglophone regions of Cameroon, Georgia, Portugal, England, Spain, China, Tanzania, and Ghana. The findings indicate that the success of asymmetric decentralization is strongly contingent upon local governance quality, particularly institutional capacity, fiscal capability, and accountability mechanisms, rather than on the breadth of devolved authority alone. This study proposes an integrative capacity-contingent framework that positions governance quality as a moderating variable linking asymmetric decentralization design to local governance outcomes, offering theoretical contribution and practical policy implications for governments designing differentiated regional autonomy arrangements.